Customer Orientation Enchances The Role of Product Innovation Capability in Improving Marketing Performance - Nada Tharia; Lauw Sun Hiong (UNHI Press, 2026)
The evolving dynamics of modern lifestyles have triggered substantial growth within the MSME sector, particularly in fashion and accessories. This phenomenon creates a promising market niche for new entrepreneurs entering the creative industry. This study primarily aims to evaluate the impact of customer orientation on marketing performance, incorporating product innovation capability as a mediating variable. The research population comprises fashion and accessory MSMEs in Pontianak City, with a sample of 153 respondents selected through purposive sampling. Data analysis was performed using Structural Equation Modeling (SEM) via AMOS version 23. The findings indicate that customer orientation has a significant effect on performance (p-value = 0.019), whereas product innovation does not significantly influence marketing performance (p-value = 0.450). Additionally, customer orientation significantly impacts product innovation (p-value = 0.001). However, product innovation fails to mediate the relationship between customer orientation and marketing performance (p-value = 0.452). Focusing on customer needs serves as the primary driver for fashion MSMEs in Pontianak, as it enhances both product development and marketing performance. Although a customer-centric focus triggers innovation, such innovation does not bridge the influence of customer orientation on marketing performance.